Self-help - Moore, Lorrie (Faber and Faber, 1985)
A collection of nine ironic, bitter-sweet stories which constitute an idiosyncratic guide to female existence: "How to be an Other Woman", "How to Talk to your Mother (Notes)", "How to Become a Writer", and "The Kid's Guide to Divorce"